(untitled) (Baghdad Science Journal, 2008)
This study showed the spreading of head lice in pupils of primary schools of Al-Nassirya city. The results showed that the percentage of males infected with lice was (5.4 %) and (9 %) for females. Also was obtained difference at age groups which we found maximum percentage of infection at age between (8 – 11) year. The highest infection for the hair tall at medium tall for both sex which the ratio (35.2 %) while for both sex with ratio (25 %) for girls. While the highest percentage for straight hair was (14.8 %) for girls